Epidemiological characteristics, complications of haemodialysis patients with end-stage diabetic nephropathy in a tertiary hospital in Guizhou, China: a cross-sectional survey - Xu, Xingxiu; Yang, Nengyuan; Da, Jingjing; Li, Qian; Yuan, Jing; Zha, Yan (Frontiers in Medicine, 2024)
Introduction In China, diabetes mellitus (DM) significantly contributes to end-stage renal disease (ESRD), necessitating treatments like hemodialysis. This study investigates hemodialysis outcomes in diabetic nephropathy patients in Guizhou Province, aiming to enhance care for this high-risk group. Methods The cross-sectional survey design to screen haemodialysis patients with end-stage diabetic nephropathy， A structured questionnaire was designed.The collected data were collated and coded and analysed using GraphPad Prism 9.5.0(730). Results Patients with end-stage diabetic nephropathy undergoing dialysis are primarily concentrated in the middle-aged and elderly population, with a higher proportion of males than females. Male patients also have a higher history of smoking and alcohol consumption compared to females. The disease progression from diabetes to diabetic nephropathy and from nephropathy to end-stage renal disease varies, with a lower dialysis vintage. Hemodialysis is the most commonly chosen treatment modality, with the highest proportion of patients selecting non-tunneled catheters. However, among patients receiving dialysis, the proportion of autogenous arteriovenous fistula (AVF) is the highest. With the increase in the duration of diabetes, the prevalence of multiple complications also increases. Conclusions Early intervention and management strategies are crucial for diabetic nephropathy patients in Guizhou, considering the rapid disease progression to ESRD and high complication rates. The study underscores the need for targeted healthcare policies to address the unique challenges of this population, with future research required to deepen the understanding of disease mechanisms and improve patient outcomes. Keywords:Diabetes mellitus；Diabetic nephropathy; End-stage diabetic nephropathy;Vascular access;multiple complications.